Investigation of attachment representations and personality traits of individuals with alcohol and substance use disorder by drawing pictures: projective research - Gül, Kübra; Demir, Volkan (Journal of Dependence, 2025)
Objective: The aim of this study was to examine attachment representations and personality traits of individuals with alcohol and substance use disorders using the drawing method. Method: The study involved 128 participants. The experimental group comprised 63 men, aged 18-65, who were receiving inpatient or outpatient treatment for alcohol and substance use disorders. The control group consisted of 65 men and women, aged 18-65, without alcohol or substance use disorders. Data were collected using the Draw-a-Bird’s-Nest Test, the Draw-a-Cactus Test, and a demographic information form.. Results: Individuals with alcohol and substance use disorders exhibited more insecure attachment representations compared to the control group. They also showed lower self-confidence and greater impulsivity. In contrast, the control group demonstrated higher levels of extroversion, cheerfulness, and optimism. Conclusion: The findings suggest that the drawing method can provide valuable insights into the attachment representations, personality traits, internal emotional states, and aggression tendencies of individuals with alcohol and substance use disorders.